Gogoli's Penalty in Renewing Death Criminal Sanctions to Immigrants of Narcotics Crimes in Indonesia (Study on the Age of Buton) - La Ode Bunga Ali; Muh Sutri Mansyah (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
Currently, the country of Indonesia is experiencing unresolved narcotics problems. various efforts to eradicate and prevent narcotics have been done, but have not caused a deterrent effect in law enforcement. There is a difficulty in eradicating it to its roots, it becomes one of the obstacles experienced by our law enforcement officers, in this study using normative juridical research method with historical approach, conceptual approach which has been studied the customary criminal sanction which is applicable during the reign of the Buton sultanate and obstacles in the application of gogoli punishment. The results of this study indicate that the renewal of national criminal law in relation to criminal sanctions may originate from customary law prevailing in the sultanate of buton as intended is gogoli punishment, while the concept of gogoli punishment is a rope encircled on the body of a person convicted and withdrawn by in opposite direction until the loss of endurance or death, the punishment is included in the type of death penalty, this is relevant to immigrants who commit a narcotics criminal act in Indonesia which has been sentenced to death several times but apparently until now still not cause effects, the authors has the hope that the punishment can be applied nationally considering narcotic criminal acts that occur almost throughout the region and will damage the morale of the nation today.